Development and validation of an organizational citizenship behavior instrument among secondary school teachers in Malaysia - Ismail, Suriani (2021)
Organizational citizenship behavior (OCB) refers to the behavior of employees, which typically exceeds their official duties and helps to increase organizational performance. Many studies on OCB have been conducted in organizations, however, scholars have only developed validated OCB scales in the Western context. Hence, the accuracy of the items used in the studies in the Malaysian context is arguable. In fact, scholars have agreed that OCB is operationally defined by an individual’s perception, which may vary based on cultural and social rules. Furthermore, limited literature was found on the context of educational practices. Therefore, the purpose of this study is to develop and validate a Malaysian version of a teachers’ OCB instrument. The instrument was named as the Teacher OCB Instrument (TOCBI). In addition, the study describes genuine scenarios of secondary school teachers’ OCB in Malaysia. A comprehensive review of the literature has identified a factor that can potentially influence OCB, which is school climate. This study is conducted in two phases: qualitative and quantitative. An exploratory sequential-mixed methods design was employed, accorded with DeVellis’s (2012) scale development guideline. Three sessions of focus group discussions (FGD) were conducted with 14 teachers for the qualitative study. The results of the qualitative study revealed seven themes of OCB which are 1) altruism; 2) courtesy, 3) conscientiousness, 4) civic virtue, 5) sportsmanship, 6) self-development, and 7) individual initiative. Then, TOCBI was validated using the content validity index (CVI) by 20 experts. Questionnaires were administered to secondary school teachers for construct validation. A total of 269 questionnaires at the exploratory stage and 824 questionnaires at the confirmatory stage were collected and analyzed. The psychometric properties of TOCBI were examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The CFA showed that the four-factor solution met the model fit with all factor loadings exceeding .50 and the final model demonstrated a good fit with more than three fit indices established at a high upper cut-off value of .90. Furthermore, the results of this study confirmed the convergent and discriminant validity. The final model revealed four dimensions of TOCBI which are civic virtue, interpersonal facilitation, individual initiative and interpersonal harmony. Descriptive statistics in terms of frequencies, percentages, means and standard deviations were used to describe the scenario of OCB among secondary school teachers in Malaysia. Findings revealed that the level of OCB among secondary school teachers was moderate. In addition, the levels of the four TOCBI dimensions were also measured. A comparison of the mean scores between the four factors of OCB showed that interpersonal facilitation was the highest type of OCB exhibited by teachers, followed by interpersonal harmony, civic virtue and individual initiative. In validating the newly developed OCB, the instrument was tested with the school climate. The findings show that there was a moderate, significant positive relationship between school climate and OCB. Hence, the results of this study support the research hypothesis whereby school climate influences teachers’ OCB. The discussion above shows that the current study has fully achieved the research objectives. Significantly, this study came out with a newly developed instrument to accurately measure teachers’ OCB in Malaysia. Moreover, this study produced fresh insight on the context of teachers in Malaysia to gain a better understanding of the relationship between school climate and OCB. It provides a new, reliable and validated teachers’ OCB instrument. In addition, this study extends the existing body of knowledge within human resource, organizational research and educational research. This study is beneficial to human resource practitioners to develop and design an appropriate program to promote teachers’ OCB and improve the level of OCB among teachers for success and prosperity. School administrators and practitioners may use the findings to formulate strategies to manage teachers’ OCB in order to increase teachers’ performance in school.